Perlindungan Hukum Pekerja Terhadap Pekerja Di Indonesia - Muhammad Fitra Hardinata; Siti Badariah; Dini Oktafiana; Mellyana Candra (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
Workers are people who do work to produce goods or services to meet the needs of themselves, their families and society by receiving wages in the form of money or other forms. Workers' rights are regulated in article 88 paragraph (1) of Law no. 13/2003 states firmly and clearly that every worker or laborer has the right to obtain protection. This research uses a standard legal approach. The data analyzed is qualitative, the data used is secondary data. This study focuses on how labor law protects efficiency and fairness in the workplace. Efficiency, effectiveness and efficiency are the four main components of labor law identified by this study. This research discusses various aspects of labor protection and efficiency in the context of labor law in Indonesia. This research also highlights the prohibition on layoffs based on economic reasons and emphasizes the importance of providing compensation to workers in the event of layoffs due to efficiency, especially in emergencies such as public health emergencies. Researchers also investigated the effectiveness, efficiency, and shortcomings of labor protection institutions, emphasizing the need for fair treatment of workers. This research does not explicitly outline specific termination indicators in the context of employment law and worker protection. The main focus is on the prohibition of layoffs for economic reasons, the importance of providing compensation to workers in the event of layoffs due to efficiency, and the role of labor law in societal development. Therefore, this study does not provide detailed indicators of desirability in this specific context.